Identification of key genes controlling soluble sugar and glucosinolate biosynthesis in Chinese cabbage by integrating metabolome and genome-wide transcriptome analysis - Wang, Lixia; Zhang, Shu; Li, Jingjuan; Zhang, Yihui; Zhou, Dandan; Li, Cheng; He, Lilong; Li, Huayin; Wang, Fengde; Gao, Jianwei (Frontiers in Plant Science, 2022)
Soluble sugar and glucosinolate are essential components that determine the flavor of Chinese cabbage and consumer preferences. However, the underlying regulatory networks that modulate the biosynthesis of soluble sugar and glucosinolate in Chinese cabbage remain largely unknown. This study observed high glucosinolate and carotene content in yellow inner-leaf Chinese cabbage, which showed a lower soluble sugar content. The differences between the yellow and the white inner-leaf Chinese cabbage were compared using the untargeted metabonomic and transcriptomic analyses in six cultivars of Chinese cabbage to explore the metabolic basis of glucosinolate and soluble sugar. Aliphatic glucosinolate and two soluble sugars (fructose and glucose) were the key metabolites that caused the difference in Chinese cabbage's glucosinolate and soluble sugar. By integrating soluble sugar and glucosinolate-associated metabolism and transcriptome data from three yellow inner-leaf Chinese cabbage and three white inner-leaf Chinese cabbage at the heading stage, we constructed complex regulatory networks to identify critical structural genes and transcription factors. These findings provide novel insights into glucosinolate and soluble sugar biosynthesis and a possible explanation for the significant difference in nutrients between yellow and white inner-leaf Chinese cabbage. Moreover, it will facilitate genetic modification to improve the Chinese cabbage's nutritional and health values.